Extraordinary diversity of the CD28/CTLA4 family across jawed vertebrates - Quiniou, Sylvie M. A.; Clark, Thomas; Bengtén, Eva; Rast, Jonathan P.; Ohta, Yuko; Flajnik, Martin; Boudinot, Pierre (Frontiers in Immunology, 2024)
Members of the CD28 family are critical for the control of immune cell activation. While CD28 and CTLA4 were previously identified in teleost fish, most members of the CD28 family have been described only in tetrapods. Using a comparative genomics approach, we found (co)orthologs of all members of the CD28 family both in Chondrichthyes and basal Osteichthyes groups, but not in Agnathans. Four additional members of the family were identified, which were present in both Chondrichthyes and Osteichthyes, some even in the tetrapod lineage but all of them absent in human. Herein, we extend the composition of the jawed vertebrate CD28 family to nine members: CD28, CTLA4, ICOS, CD28H, CD28HL1, CD28HL2, CD28HL3, CD28X and PD-1. Each of these genes had a single extracellular IgSF V domain, and conserved motifs in the V and the cytoplasmic domain. While a genomic cluster of three consecutive genes like CD28/CTLA4/ICOS was conserved across jawed vertebrates except in teleosts, the other members of the CD28 family were located on multiple chromosomes. Our findings show that these co-stimulatory/co-inhibitory receptors likely arose in early jawed vertebrates, and diversified when the Ig/TCR/MHC-based adaptive immunity emerged, heralding the advent of complex regulatory networks controlling lymphocyte activation.